1989
DOI: 10.1136/hrt.62.6.462
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac involvement in Churg-Strauss syndrome shown by echocardiography.

Abstract: SUMMARY To define the range of cardiac involvement in the Churg-Strauss syndrome, M mode, continuous wave Doppler, and cross sectional echocardiograms were recorded in twelve patients with the disorder. The M mode recordings were digitised and the cross sectional images were recorded with standardised gain settings to determine regional myocardial echo amplitude. Left ventricular end diastolic and end systolic dimensions were increased above the normal 95% confidence interval in four patients, three of whom sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 16 publications
2
30
0
1
Order By: Relevance
“…[3,4]. In a small series of 12 patients with Churg-Strauss syndrome, subendocardial involvement was not found in echocardiography [5]. However, it could be assumed that marked endocardial thickening or restrictive filling pattern are necessary for visualization by echocardiography.…”
Section: Discussionmentioning
confidence: 96%
“…[3,4]. In a small series of 12 patients with Churg-Strauss syndrome, subendocardial involvement was not found in echocardiography [5]. However, it could be assumed that marked endocardial thickening or restrictive filling pattern are necessary for visualization by echocardiography.…”
Section: Discussionmentioning
confidence: 96%
“…Although pulmonary in ltrate is present in the diagnosis of 37.5% of the series of Guillevin et al, 8 in our case we found no evidence. In 1989, Morgan et al 11 carried out an echocardiographic study in 12 patients with CSS; they found a decrease in the shortening fraction of the right ventricle in four patients, and mitral insuf ciency in six patients; however, they did not nd signs of subendocardial involvement similar to the hypereosinophilic syndrome. No evidence of extravascular granulomas was found.…”
Section: Discussionmentioning
confidence: 99%
“…30 Morbidity and mortality are often due to cardiac or gastrointestinal complications and respiratory failure. [30][31][32] Pathological findings in CSS are necrotizing small-vessel vasculitis and eosinophilic inflammatory infiltrate with necrotizing granulomas. 33,34 Some investigators have suggested an association between leukotriene inhibitors and CSS, 35,36 but currently the most widely accepted hypothesis is that the use of leukotriene inhibitors permits corticosteroid dose reductions, which unmasks previously unrecognized CSS that was already being treated with corticosteroids.…”
Section: Cssmentioning
confidence: 99%